Book Review: Deterrence before Hiroshima: the airpower background of modern strategy (1966): Deterrence before Hiroshima: the airpower background of modern strategy, by George H. Quester (New York and London: Wiley, 1966). Issue 472 (4th May 2018) - Howard, Michael
Abstract : With the death of Professor Sir Michael Howard, The International Institute for Strategic Studies (IISS) lost not only its president emeritus but the last of its founders and intellectual parents. The foremost military historian of his generation, Sir Michael embodied and epitomised a historical sensibility that informed all his writing. He will forever remain an icon not only for historians, but for all those who acknowledge the indispensability of history and the historical sensibility for any true understanding of present events. In tribute to Sir Michael and in celebration of his life and work, this Adelphi book collects a selection of his remarks and writings for IISS publications over six decades, as well as previously unprinted material. Through this collection, these works will reach a new generation of readers and be made more accessible to those fortunate enough to have read them already. They illustrate Sir Michael's role in the Institute's creation and his abiding presence in its evolving intellectual life, and serve as a historical document, tracing the development of strategic thought and preoccupations from the 1950s to the recent past. In addition to their historical value, Sir Michael's conclusions retain their immediacy and power. This book is therefore of direct relevance to anyone interested in contemporary events: whether the professional analyst, the student of international relations or the general reader. 'This wonderful collection, containing pieces written by Sir Michael Howard over 60 years, will be enjoyed by his, and the Institute's, many friends and admirers. Here will be found many reminders, written with Michael's customary lucidity, of the big issues of the post-war period as they were seen at the time. In addition to a fascinating interview conducted not long before his death about the origins of the Institute, there are obituaries of many of the key and now too often forgotten figures of those early years.' — Sir Lawrence Freedman, Emeritus Professor of War Studies, King's College London 'Sir Michael's exploration of policy judgement by fusing politics, strategy, history, ethics, and technology in the nuclear age is increasingly relevant in this complex age of artificial intelligence. His interdisciplinary approach continues to be a guide as we work to synthesize and solve the challenges presented by rapid technological advancements. The pieces contained here show both the continued relevance of his work, and his commitment to studying military history properly, in "depth", in "width", and in "context".' — Dr Yoichi Funabashi, Chairman of Asia Pacific Initiative